PERANAN OBAT GOLONGAN STATIN TERHADAP LUARAN STATUS FUNGSIONAL PASIEN STROKE ISKEMIK BERULANG DI RUMAH SAKIT BETHESDA YOGYAKARTA - ALEXXANDER, . ([Yogyakarta] : Universitas Gadjah Mada, 2015)
BACKGROUND: The proportion of patients who were taking statins when they first entered the hospital with recurrent ischemic stroke increasing rapidly . Although the use of statins is popular used in hospitals but still occur controversy over the use of statins in stroke. This is the background of further research on the effect of statin use on the outcomes of functional status in patients with recurrent ischemic stroke . OBJECTIVE: To identify the role of statin therapy to gain good outcomes of functional status in patients with recurrent ischemic stroke in Bethesda Hospital Yogyakarta METHODS: This study is a retrospective cohort analysis method using the data of medical records of patients. As a selected sample group of recurrent ischemic stroke patients, both of which received treatment with statins or who do not get statin treatment. Then observed effect of statin use on the outcomes of the patient's functional status. The number of subjects for each group was 77 patients. Outputs well marked with mRS score 0-3, while bad outcomes are marked with 4-6. The location of research is in the Bethesda hospital in Yogyakarta. Statistical analyzes were performed using SPSS v.20.0 software. The results of the study will be presented in three parts: the basic characteristics of the statin group and the nonstatin, the results of bivariate analysis to see which variables have association to functional status outcomes, and predictor factors of good functional status was further analyzed by multivariate logistic regression analysis. RESULTS: The use of statins in patients with recurrent ischemic stroke can provide good functional status outcomes at Bethesda Hospital Yogyakarta (p = 0.022